Condition of coral reefs in the Guanahacabibes National Park, Cuba - Perera Valderrama, Susana (2013)
In 2007, a health assessment of coral reefs in the Guanahacabibes National Park, Cuba, was conducted based on the condition of coral communities. Coral condition indicators (maximum diameter, species richness, diseases and mortality) were evaluated, at different depths in 13 sites with varying exposure levels to the main ocean-atmospheric phenomena that generate waves in the area (north, south and trade winds). Forty two species of stony corals were identified. The most abundant species were Siderastrea siderea, Montastraea faveolata, Agaricia agaricites and Porites astreoides. The average coral cover varied between 4.8% and 31.2%, with a general average of 17%. The integrated analysis of all condition indicators of coral communities suggested the existence of two distinctive areas according to wind exposure and the consequent effect of both waves and sediments. The first area, covering east of Bahía de Corrientes (between Uvero Quemado and Cuevas de Pedro), was more protected and had a more favorable environment, as suggested by the biological indicators. The second area was comprised of the western part, was more exposed (between Veral and Faro Roncali), and showed the highest relative cover of species resistant to sedimentation, especially at 10 and 15 m deep. These results indicate that coral reefs at the Guanahacabibes National Park do not escape from the degradation process faced by most coral reefs in the Caribbean region.